Changes in the prevalence and correlates of menthol cigarette use in the USA, 2004–2014. (11th October 2016) - Villanti, Andrea C; Mowery, Paul D; Delnevo, Cristine D; Niaura, Raymond S; Abrams, David B; Giovino, Gary A
Abstract : Introduction: National data from 2004 to 2010 showed that despite decreases in non-menthol cigarette use prevalence, menthol cigarette use prevalence remained constant in adolescents and adults and increased in young adults. The purpose of the current study was to extend these analyses through 2014. Methods: We estimated the prevalence of menthol cigarette smoking in the USA during 2004–2014 using annual cross-sectional data on persons aged ≥12 years from the National Survey on Drug Use and Health. Self-reported menthol status for selected brands that were either exclusively menthol or non-menthol were adjusted based on retail sales data. Data were weighted to provide national estimates. Results: Although overall smoking prevalence has decreased, the proportion of past 30-day cigarette smokers using menthol cigarettes was higher (39%) in 2012–2014 compared to 2008–2010 (35%). Youth smokers remain the most likely group to use menthol cigarettes compared to all other age groups. Menthol cigarette prevalence has increased in white, Asian and Hispanic smokers since 2010. Menthol cigarette prevalence exceeded non-menthol cigarette prevalence in youth and young adult smokers in 2014. Among smokers, menthol cigarette use was positively correlated with co-use of cigars. Menthol cigarette and smokeless tobacco co-use also increased from 2004 to 2014. Conclusions: The youngest smokers are most likely to use menthol cigarettes. Among smokers, increases in overall menthol cigarette use and menthol cigarette use in whites, Asians and Hispanics since 2010 are of concern. There is tremendous urgency to limit the impact of menthol cigarettes on public health, particularly the health of youth and young adults.